Perancangan Aplikasi Inventaris Barang Habis Pakai Berbasis Android di SMP Negeri 1 Talang - Mochamad Alendaula; Rudi Heryanto (Prodi Teknik Informatika Universitas Pasir Pengaraian, 2026)
The management of consumable goods inventory at SMP Negeri 1 Talang is currently still carried out conventionally using manual bookkeeping, making it vulnerable to data loss risks, reporting delays, and stock inaccuracies. This study aims to design and build an Android-based consumable goods inventory application to improve the efficiency and accuracy of data management in real-time. This system was developed using Android Studio with the Kotlin programming language and Firebase as the global database. The system testing methods used were Black Box Testing to test functionality and User Acceptance Testing (UAT) to test user aspects. The Black Box testing results showed that all system functions ran 100% according to the design. Meanwhile, the UAT testing results obtained a score of [85%], falling into the